Improvement Of Block Product Turbo Coding By Using A New Concept Of Soft Hamming Decoder - Alaa Ghaith (European Scientific Journal, ESJ, 2016)
The block product turbo code (BPTC) is classified as one of block turbo code concatenation forms. The Hamming code can detect two-bit error and correct one-bit error. The BPTC uses two Hamming codes for "column" coding and "row" coding, it has improved the Hamming code correcting only one error. In addition, the BPTC carries out block interleaving coding for disorganizing the transmission sequence before transmission, so as to avoid burst errors when the signal meets multi-path channel in the channel. This paper will discuss the decoding mechanism of the BPTC and analyze the efficiency of using a soft decoding algorithm in the decoding process. The soft Hamming Decoder is based on error patterns which belong to the same syndrome. It is shown that it is sufficient to investigate error patterns with one and two errors to gain up to 1.2 dB compared to hard decision decoding. Here, we will consider also the error patterns with three errors which belong to the determined syndrome, which increases the gain and improves the quality of the soft-output due to the increased number of comparisons with valid code words, in despite that, it will increase the complexity of the decoding process. The system is based on two Hamming block channel code combinations, which can be similar or different, a block interleaving to construct a BPSK modulation and BPTC coding system in the concept of feedback encoding in turbo code over an AWGN channel. To observe its coding improvement, we present the simulation results for the soft decoding of the BPTC codes of a code word length from 49 bits (using two (7,4) codes) up to 1440 bits (using two (127,120) codes).